Drop-out and admission cancel rate among the students in a selected medical college - Wahed, F; Latif, SA; Mahamud, MM; Nessa, A; Hossain, MA; Sultana, SZ; Hossain, MB (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 197-200. The abstract of this article is available on the PubMed website